The Effect Of Workload And Work-Life Balance On Work Motivation Of Inpatient Nurses At Haji Hospital, South Sulawesi Province In 2024 - Sulistya Kalpeing, Claudya Emma; Indahwaty AS, Andi; Rivai, Fridawaty; Pasinringi, Syahrir Andi; Irwandy, Irwandy; Arifah, Nur (Journal of Neonatal Surgery, 2025)
Background: Nurses' performance that has not reached the standards of the Indonesian National Nurses Association (PPNI) is one indicator of problems with work motivation. Low work motivation can be influenced by an imbalance between work and personal life demands (work-life balance), as well as the high workload experienced by nurses. At the Haji Regional Hospital in South Sulawesi Province, this issue is important because a good work-life balance can improve the welfare and productivity of nurses. Conversely, excessive workload has the potential to reduce motivation, disrupt performance, and impact the quality of nursing services. Objectives: To analyze workload, work life balance affects the work motivation of nurses at the Haji Regional Hospital, South Sulawesi Province. Method: This study used a quantitative approach with a cross-sectional design in the Inpatient Installation of RSUD Haji, South Sulawesi Province using exhausted sampling on 104 nurses, data were collected through questionnaires and analyzed using the chi-square test and path analysis to measure the magnitude of direct and indirect effects. Results: The results of this study indicate that workload and work-life balance affect work motivation. The direct effect of workload on work motivation is higher than the indirect effect through work-life balance. Conclusion: Workload has a major effect on work motivation, stress management training, psychological support and adjusting the nurse's workload to the patients being treated are needed.